Classroom Communication in ELT - The Role of Mother Tongue - Hrubý, Jan (Univerzita Pardubice, 2013)
This work focuses on classroom communication, more specifically on the comparison of the use of English and the mother tongue in English language teaching. The theoretical part of this thesis focuses at first on the development of language teaching as a whole followed by the methodological development based on its underlying theories and also the role the teacher and the language plays. Throughout the theoretical part, many suggestions and questions arise. They are being dealt with in the practical part where these suggestions are compared with a teaching practice through observation of a teaching process in a selected primary school and interviews with the teachers.
Komunikace v hodinách anglického jazyka - role mateřského jazyka
Keywords: mateřský jazyk; osvojování cizího jazyka; mother tongue; English language teaching; communication; development; second language acquisition; vyučování anglického jazyka; komunikace; vývoj